2022
DOI: 10.3390/brainsci12111500
|View full text |Cite
|
Sign up to set email alerts
|

Hand and Foot Selection in Mental Body Rotations Involves Motor-Cognitive Interactions

Abstract: Action imagery involves the mental representation of an action without overt execution, and can contribute to perspective taking, such as that required for left-right judgments in mental body rotation tasks. It has been shown that perspective (back view, front view), rotational angle (head-up, head-down), and abstractness (abstract, realistic) of the stimulus material influences speed and correctness of the judgement. The present studies investigated whether left-right judgements are more difficult on legs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…One might expect lower imagery ability in patients with apraxia than in healthy controls, as has been shown in a single case study using a hand laterality judgment task [50]. Moreover, we would expect differences between patients and healthy controls to be larger in objective measures such as the mental body-rotation task [51] or the presented mental paper-folding task than in questionnaires that are prone to self-rating biases [14]. Nevertheless, it could be interesting to investigate potential correlations with existing questionnaires on action imagery ability [52], such as the Vividness of Movement Imagery Questionnaire [48,53].…”
Section: Discussionmentioning
confidence: 88%
“…One might expect lower imagery ability in patients with apraxia than in healthy controls, as has been shown in a single case study using a hand laterality judgment task [50]. Moreover, we would expect differences between patients and healthy controls to be larger in objective measures such as the mental body-rotation task [51] or the presented mental paper-folding task than in questionnaires that are prone to self-rating biases [14]. Nevertheless, it could be interesting to investigate potential correlations with existing questionnaires on action imagery ability [52], such as the Vividness of Movement Imagery Questionnaire [48,53].…”
Section: Discussionmentioning
confidence: 88%
“…A similar sample size (N = 146) has previously been shown to suffice for the proposed analyses (Muraki & Pexman, 2021). The motor imagery data collected for this study were also reported in Dahm et al (2022). After data cleaning there was an average of 152.1 participants per noun (SD = 2.1) and 84.0 nouns per participant (SD = 0.9) in the BOI SCT.…”
Section: Participantsmentioning
confidence: 79%
“…There are concerns about motor imagery questionnaires that measure imagery using participants' self-report, such as the potential for social desirability effects, overestimation of ability, and lack of self-awareness to provide accurate assessments of ability (Dahm, 2020). Measures that are not subject to these self-report biases include the mental body rotation task (MBRT; Dahm, 2020;Dahm et al, 2022), the hand laterality judgement task (HLJT; Parsons, 1987) and final position selection tasks such as the Test of Ability in Movement Imagery (TAMI; Madan & Singhal, 2013). In the present studies, we used four objective motor imagery measures.…”
Section: Introductionmentioning
confidence: 99%
“…Equivalent performance for both groups was found in a letter rotation task, emphasizing intact mental rotation in the autistic group. Chen et al (2018) suggested that the discrepancy in findings could be due to the use of simpler stimuli reducing the engagement of MI ( Dahm et al, 2022 ): Conson et al (2013) used line drawing stimuli rather than 3D color images or photos and presented the hands in the back view only as opposed to front and back. This suggestion is supported by the lack of RT differences, suggesting that the autistic group found the task less complex and potentially used a strategy that did not involve MI.…”
Section: Resultsmentioning
confidence: 99%
“…Non-autistic participants were more accurate and faster when judging back than front facing figures whereas the reverse was true for the autistic participants. This advantage for back facing figures is thought to be due to participants more easily imaging themselves into the position of the body presented, as opposed to either using mental object rotation strategies or needing to initially rotate oneself before superimposing one’s body on the image in front facing images ( Kessler and Thomson, 2010 ; Conson et al, 2015 ; Dahm et al, 2022 ). Conson et al (2015) suggest that the pattern reflects autistic individuals using a non-embodied mental object rotation strategy for both views, which is supported by a jump in RTs between 90 and 180 degree angles in the back facing view for the non-autistic group only.…”
Section: Resultsmentioning
confidence: 99%